RELATIONSHIP OF GROWTH FACTORS WITH THE DEVELOPMENT OF IRON DEFICIENCY ANEMIA IN GIRLS TEENAGERS (International Journal of Scientific Pediatrics, 2023)
Annotation: According to the World Health Organization, in any population, for every person suffering from IDA, there are three with iron deficiency (IAD). The risk group for the development of anemia includes children, women of reproductive age and the elderly. A special group among them are girls of pubertal age, who have a high potential for the formation of various organ dysfunctions. The purpose of this work was to study the clinical and anamnestic features of the dynamics and transformation of iron deficiency anemia in adolescent girls. Object and methods of the study: adolescent girls aged 12-14 years (n=177) of the Uzbek population, respectively, with LAD (45), mild IDA (56) and moderate (25), and the control group (51). For the study, whole blood and serum of adolescent girls with IDA were used. General clinical, instrumental, biochemical and statistical methods were used. Results: From the data of our material it follows that the clinical picture of IDA in schoolgirls was somewhat transformed and among them the syndrome of decreased immunological resistance of the body and gastrointestinal syndrome began to prevail, their frequency increased by more than 2-5 times compared to the above authors. The clinical picture of iron deficiency anemia in adolescent girls is characterized by polymorphism of symptoms and syndromes, which indicates the involvement of many organs and systems in the pathological process. It is concluded that it is necessary to update data on the clinical symptoms of ID in adolescent girls, depending on age, gender and regions of residence.
Keywords: adolescent girls; iron deficiency; anemia; transformation of clinical signs